Enhanced resistive switching in forming-free graphene oxide films embedded with gold nanoparticles deposited by electrophoresis. (23rd November 2015) - Khurana, Geetika; Misra, Pankaj; Kumar, Nitu; Kooriyattil, Sudheendran; Scott, James F; Katiyar, Ram S
Abstract: Forming-free resistive random access memory (ReRAM) devices having low switching voltages are a prerequisite for their commercial applications. In this study, the forming-free resistive switching characteristics of graphene oxide (GO) films embedded with gold nanoparticles (Au Nps), having an enhanced on/off ratio at very low switching voltages, were investigated for non-volatile memories. The GOAu films were deposited by the electrophoresis method and as-grown films were found to be in the low resistance state; therefore no forming voltage was required to activate the devices for switching. The devices having an enlarged on/off ratio window of ∼10 6 between two resistance states at low voltages (<1 V) for repetitive dc voltage sweeps showed excellent properties of endurance and retention. In these films Au Nps were uniformly dispersed over a large area that provided charge traps, which resulted in improved switching characteristics. Capacitance was also found to increase by a factor of ∼10, when comparing high and low resistance states in GOAu and pristine GO devices. Charge trapping and de-trapping by Au Nps was the mechanism responsible for the improved switching characteristics in the films.